Communication System for Electric Energy Data Acquisition System of SGWM-Based 230 MHz Wireless Broadband Communications Key Technology - Lijun Dong; Qian Zhang; Enguo Zhu; Xuan Liu (Dianxin kexue)
Electric energy data acquisition system is an important part of smart grid.Against the problem of the communication way of the 230 MHz wireless private network in the electric energy data acquisition system,low communication rate,fewer access points,low acquisition success rate,poor real-time performance,the technical proposal of the SGWM-based 230 MHz wireless broadband communications key technology of the communication system for the electric energy data acquisition system was proposed.The communication network technologies,such as the carrier aggregation technology,smart routing technology,networking technology,were discussed.The SGWM wireless communications technology in the electric energy data acquisition system was elaborated.By designing and analyzing networking scheme,the result indicates that the field application effect of the SGWM-based 230 MHz wireless broadband communications key technology in the electric energy data acquisition system is very good.Thus it provided technical support for the propel of the information bidirectional interaction and construction of the strong smart grid.